2011
DOI: 10.1007/s10164-011-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Condition dependence of male nuptial gift construction in the spider Pisaura mirabilis (Pisauridae)

Abstract: Pisaura mirabilis males offer a prey wrapped in silk as a nuptial gift that functions as a male mating effort. If nuptial gift construction is costly, males in poor feeding condition would invest less in this behaviour than males in good condition. We investigated frequencies and characteristics of gift construction in males under different sexual stimuli and different feeding conditions. We analysed gift construction behaviours of 17 males exposed sequentially to three treatments: female silk (S), female silk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
1
26
0
2
Order By: Relevance
“…Consistent with prior work, we observed a significant reduction in sigmoid displays in the restricted diet group (Devigili et al 2012), suggesting that this component of male sexual behavior exhibits condition dependence and therefore may provide an honest signal of male quality (van Oosterhout et al 2003;Kolluru and Grether 2005;Kolluru et al 2009;Head et al 2010). Our results also revealed that male sexual interest was influenced by diet (see also Kolluru et al 2009;Albo et al 2011;Devigili et al 2012), suggesting that in guppies, as with some other species, courtship effort is a reliable indicator of male condition (e.g., Shine and Mason 2005;Shamble et al 2009;Kloskowski et al 2012). Furthermore, as with Devigili et al's (2012) study, our results revealed no significant effect of diet quantity on the frequency of gonopodial thrusts.…”
Section: Effect Of Diet On Precopulatory Traitssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior work, we observed a significant reduction in sigmoid displays in the restricted diet group (Devigili et al 2012), suggesting that this component of male sexual behavior exhibits condition dependence and therefore may provide an honest signal of male quality (van Oosterhout et al 2003;Kolluru and Grether 2005;Kolluru et al 2009;Head et al 2010). Our results also revealed that male sexual interest was influenced by diet (see also Kolluru et al 2009;Albo et al 2011;Devigili et al 2012), suggesting that in guppies, as with some other species, courtship effort is a reliable indicator of male condition (e.g., Shine and Mason 2005;Shamble et al 2009;Kloskowski et al 2012). Furthermore, as with Devigili et al's (2012) study, our results revealed no significant effect of diet quantity on the frequency of gonopodial thrusts.…”
Section: Effect Of Diet On Precopulatory Traitssupporting
confidence: 91%
“…; Albo et al. ; Devigili et al. ), suggesting that in guppies, as with some other species, courtship effort is a reliable indicator of male condition (e.g., Shine and Mason ; Shamble et al.…”
Section: Discussionmentioning
confidence: 99%
“…In P. mirabilis , copulation duration correlates positively with the amount of sperm transferred (Drengsgaard & Toft, ; Albo et al ., ). Female nuptial gift consumption was shown to determine copulation duration (Lang, ; Stålhandske, ), and copulation duration was significantly longer when males offered genuine gifts compared to worthless gifts (Albo et al ., ). In accordance with a response to increased sperm competition, we found an increase in the frequency of genuine gifts over the season.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, males that offer worthless gifts are equally likely to be accepted by females as males that offer a genuine gift, at least when females are unmated (Albo et al ., ). If worthless gifts are less costly to produce, this should favour the worthless gift‐giving tactic in the population, as seen in dance flies (Empididae; Preston‐Mafham, ; LeBas & Hockham, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation